2023
DOI: 10.33844/ijol.2023.60347
|View full text |Cite
|
Sign up to set email alerts
|

The Improving Role of Digital Leadership in the Impact of Social Loafing on Job Performance

Abstract: It is possible to define digital leadership as a type of leadership that is informed about digital technologies that help the digital transformation of employees and businesses and is also fed by modern leadership theories. The concept of digital leadership has come to the fore, particularly with Industry 4.0. Digital leadership is seen as an element that positively affects organizational culture and helps the development of the organization. Following the Covid-19 pandemic, businesses have experienced a consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Digital leaders are expected to transform organizations innovatively and adapt them to contemporary conditions, as well as to increase their performance by managing organizations effectively throughout the process [2]. Research conducted with employees to direct the process in question indicated a high level of belief (77%) that change can be made in organizations through new leaders [3], which was also supported by a report prepared by the European Union stating that there was a need for 40,000 to 50,000 digital leaders every year from 2015 until 2020 [4,5]. Countries with a strategic perspective allocate significant financial resources to digital transformation.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Digital leaders are expected to transform organizations innovatively and adapt them to contemporary conditions, as well as to increase their performance by managing organizations effectively throughout the process [2]. Research conducted with employees to direct the process in question indicated a high level of belief (77%) that change can be made in organizations through new leaders [3], which was also supported by a report prepared by the European Union stating that there was a need for 40,000 to 50,000 digital leaders every year from 2015 until 2020 [4,5]. Countries with a strategic perspective allocate significant financial resources to digital transformation.…”
Section: Introductionmentioning
confidence: 93%
“…Excessive workforce needs and considerable financial factors requiring management have fostered an increasing interest in digital leadership studies. Although the positive effect of digital leadership on job performance is known [5,7,8], the mediating role of innovative behavior has not been fully clarified in the literature. Therefore, determining the mediating effect in question constitutes one of the aims of the present study.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of digital leadership for business and public organizations is in cluster-1. The discussion contained in the cluster is divided into digital transformation [41], [42], [43], [44], [45], [46], [47], [48], the correlation of digital leadership to performance [49], [50], a digital leadership framework for organizations [51], [52], and an overview of the concept of digital leadership [53], [54].…”
Section: What Is the Effect Of Digital Leadership In Improving Employ...mentioning
confidence: 99%
“…Four studies were conducted on private companies [57], [58], [59], [60]. Abbasov [57] viewed digital leadership as a leadership style crucial in the Industrial Revolution 4.0 era.…”
Section: What Is the Effect Of Digital Leadership In Improving Employ...mentioning
confidence: 99%
See 1 more Smart Citation